Abundance and Diversity of Seaweed in The Coastal Area of South Aceh Regency, Aceh Province - Firman Rija Arhas; Saida Rasnovi; Dahlan Dahlan (Elkawnie, 2022)
Abstract: The coastal area of South Aceh has a high level of biodiversity, one of which can be found in seaweed which plays an essential ecological and economic role. It is important to recognize the existence and diversity of seaweed as a source of data for optimal development. The present study aims to determine the composition, abundance and diversity of seaweed in the research area. It was conducted between February and October 2021. A combination of line transect and quadratic transect research methods was employed at six research locations across South Aceh’s coastal area, i.e.: Keumumu Hilir, Paya Peulemat, Ujong Nibong, Ujong Seurudong, Gunong Cut, and Pulo Dua. The findings exhibit a total of 32 species of seaweed, consisting of 11 species of the Chlorophyceae class, 11 of the Phaeophyceae class, and 10 of the Rhodophyceae class. Several seaweed species are found in the highest abundance (>20%) on the coast of South Aceh, namely Sargassum oligocystum, Amphiroa foliacea, Sargassum plagiophyllum, Amphiroa fragilissima, and Halimeda opuntia. The environmental conditions in this coastal area, based on the water quality index measured using the pollution index method, indicate the quality status of light pollution. The diversity index values range between 1.500 and 2.327 with an average of 1.949, considered as the moderate category of community diversity and stability. The uniformity index values range from 0.721 to 0.891, with an average of 0.804, considered as the high category of uniformity. The dominance index values range between 0.138 and 0.306, with an average of 0.201, considered as the low category of dominance. These conditions represent that the level of stability of the seaweed community in the coastal area of South Aceh Regency is considered good and stable. This can be referred to as a data source for biodiversity information in science, development and sustainable management of coastal areas.Abstrak: Pesisir Aceh Selatan memiliki potensi keanekaragaman hayati yang sangat beragam, salah satunya adalah rumput laut yang memiliki peranan dari sisi ekologi dan ekonomi. Keberadaan dan keragaman rumput laut sangat penting untuk diketahui sebagai sumber data untuk dikembangkan secara optimal. Penelitian ini bertujuan untuk mengetahui komposisi, kelimpahan, dan keragaman jenis rumput laut. Penelitian ini dilaksanakan pada bulan Februari hingga Oktober 2021. Metode yang digunakan adalah kombinasi metode transek garis dengan transek kuadrat pada enam lokasi penelitian di kawasan pesisir Aceh Selatan, yaitu: Keumumu Hilir, Paya Peulemat, Ujong Nibong, Ujong Seurudong, Gunong Cut, dan Pulo Dua. Hasil penelitian ditemukan 32 spesies rumput laut, dengan komposisi kelas Chlorophyceae 11 spesies, kelas Phaeophyceae  11 spesies, dan kelas Rhodophyceae 10 spesies. Spesies rumput laut yang ditemukan dengan kelimpahan tertinggi (>20 %) di kawasan pesisir Kabupaten Aceh Selatan adalah Sargassum oligocystum, Amphiroa foliacea, Sargassum plagiophyllum, Amphiroa fragilissima, dan Halimeda opuntia. Kondisi lingkungan di kawasan pesisir Aceh Selatan berdasarkan hasil pengukuran indeks kualitas air dengan penentuan metode indeks pencemaran menunjukkan status mutu cemar ringan. Nilai indeks keanekaragaman berkisar antara 1,500-2,327 dan rata-rata 1,949 dengan kategori keanekaragaman dan kestabilan komunitas sedang. Nilai indeks keseragaman berkisar antara antara 0,721-0,891 dan rata-rata 0,804 dengan kategori keseragaman yang tinggi. Nilai indeks dominansi berkisar antara 0,138-0,306 dan rata-rata 0,201 dengan nilai kategori dominansi rendah. Kondisi ini menggambarkan tingkat kestabilan komunitas rumput laut di kawasan pesisir Kabupaten Aceh Selatan tergolong baik dan stabil untuk kehidupan rumput laut. Hal ini menjadi rujukan sumber informasi keanekaragaman hayati dalam ilmu pengetahuan, pengembangan dan pengelolaan kawasan pesisir yang berkelanjutan.